The problem of multiple interpretations of the terms “Information” and “Data” in the Polish Criminal Code and its consequences - Filipkowski, Wojciech (The Opole Studies in Administration and Law, 2024)
This paper examines the legal definitions of “information” and “data” within the Polish Criminal Code (CC), highlighting their implications for criminal liability, particularly in the realm of cybercrime. The research addresses the problem of definitional ambiguity, which poses challenges to the principles of legal certainty and consistency in criminal law. The study employs a dogmatic analysis of both general and specific parts of the CC, including an evaluation of commentaries and relevant judicial decisions. Findings indicate that the interchangeable use of “information” and “data” across various provisions leads to interpretational inconsistencies, potentially broadening the scope of criminal liability in a manner that contradicts constitutional principles. Moreover, the lack of precise legal definitions complicates the application of law by practitioners and undermines efforts to standardize legal frameworks for international cooperation in combating cybercrime. The author concludes that establishing clearer definitions is essential for the effective enforcement of criminal law and the protection of fundamental rights in the digital age.